2019
DOI: 10.1101/515700
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Partial ligand-receptor engagement yields functional bias at the human complement receptor, C5aR1

Abstract: 20The human complement component, C5a, binds two different seven transmembrane receptors termed 21 as C5aR1 and C5aR2. C5aR1 is a prototypical G protein-coupled receptor that couples to Gαi sub-family 22 of heterotrimeric G proteins and β-arrestins (βarr) following C5a stimulation. Peptide fragments derived 23 from the carboxyl-terminus of C5a can still interact with the receptor, albeit with lower affinity, and can 24 act as agonists or antagonists. However, whether such fragments might display ligand bias at… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…Notably, C5a also binds and activates a second receptor, C5aR2, albeit without any detectable G-protein coupling but with robust β arrestins (βarr) recruitment 33 . Three N-terminal tyrosine residues of C5aR2 may also be sulfated, but mutations of these residues did not significantly change C5a binding to C5aR2 34 , suggesting against the two-site binding mechanism for C5aR2.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, C5a also binds and activates a second receptor, C5aR2, albeit without any detectable G-protein coupling but with robust β arrestins (βarr) recruitment 33 . Three N-terminal tyrosine residues of C5aR2 may also be sulfated, but mutations of these residues did not significantly change C5a binding to C5aR2 34 , suggesting against the two-site binding mechanism for C5aR2.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent data obtained by our laboratory suggest that TLQP-21 has a lower potency compared with the C3aR1 agonist C3a 70–77 in guinea pigs (unpublished data), suggesting that TLQP-21 can be a safer template to target C3aR1 functions in multiple cell types, including adipocytes, while minimizing side effects. Additionally, our study revealed that murinizing hC3aR1 at five residues in the receptor binding pocket is sufficient to enhance the β-arrestin potency of mTLQP-21 (48-fold) or hTLQP-21 (28-fold) to a greater extent than C3a (8.5-fold), suggesting the existence of differences in agonist-mediated activation, possibly implying a biased agonism mechanism (Lotta et al, 2019; McCorvy et al, 2018; Pandey et al, 2019), which will be explored in future studies. A therapeutically beneficial biological activity of TLQP-21 has been established for energy balance, lipolysis, sexual behavior, blood pressure regulation, and glucose homeostasis, whereas the peptide can cause pain behavior (Bartolomucci et al, 2011; Cero et al, 2016; Doolen et al, 2017; Pinilla et al, 2011).…”
Section: Discussionmentioning
confidence: 75%
“…Despite evidence from the present study and others (43) that C5a can activate tumorigenic signaling pathways, in our hands, treatment of B16.F0 melanoma cells with recombinant mC5a had minimal effects on cell proliferation and migration. It should be noted, however, that although C5a-mediated ERK and p38 phosphorylation was detectible in B16.F0 cells, much greater increases in MAPK activation are observed in myeloid cells following C5a stimulation (;50-100-fold vs. the 1.5-2-fold observed for B16.F0 cells) (32), which may explain the lack of C5a functional activity observed in vitro. Nevertheless, the growth of C5aR1-expressing B16.F0 melanoma tumors was significantly reduced in C5aR1-deficient mice compared with wild-type mice, suggesting a predominant role for C5aR1-expressing host immune cells in the antitumor response.…”
Section: Discussionmentioning
confidence: 83%
“…However, the lack of a reliable antibody (31) precluded us from confirming C5aR2 protein expression in these cells. Both ERK and p38 MAPK are wellrecognized C5aR1-mediated signaling pathways (32). Incubation of B16.F0 cells with recombinant mC5a resulted in a modest (1.5-2-fold) increase in phosphorylation of ERK and p38 MAPK( Fig.…”
Section: C5ars Are Expressed By B16f0 Melanoma Cellsmentioning
confidence: 92%